Inversion of cooling parameters for structure concrete surrounding the spiral case based on improved coati optimization algorithm - Xu, Wenjie; Wang, Gang; Ma, Zhenyue; Xian, Liquan; Zhang, Dongdong; Li, Junjie (Applied thermal engineering, 2025)
•Emphasizes the safety and reliability of the spiral case and surrounding concrete.•Establishes an objective function for cooling design.•Improved COA based on golden sine and polynomial variation (GPCOA).•Uses optimized meta-heuristic algorithm for parameter inversion.•A water pipe heat transfer element was developed and used to validate the parameters. Since the composite structure of metal spiral case and its surrounding concrete is the core of hydro-power plant and the load-bearing main body supporting large or giant turbine generation unit, it is crucial to ensure its structural safety and reliability. This study proposes an inversion method for cooling parameters based on thermodynamic theory to optimize cooling water pipe design and ensure that concrete structure temperature control complies with engineering standards. By integrating the golden sinusoidal factor and polynomial variation strategy, the Coati optimization algorithm (COA) is enhanced, resulting in the proposed GPCOA method. Its accuracy, efficiency, and robustness in high-dimensional optimization problems are validated using the CEC2014 test set and basic functions. The REINF element is employed to simulate the cooling water pipe assembly, and the cooling effect is validated through the monitor value, demonstrating the rationality of the inversion parameters. Based on the inversion results, a water pipe unit is established, and finite element simulation is conducted. The results demonstrate that the temperature of the concrete surrounding the spiral case complies with engineering design standards, the temperature drop rate is effectively controlled, thermal stress from sudden temperature changes is mitigated, and the structure’s safety and reliability are ensured. The inversion method proposed in this study, based on energy transfer principles, overcomes the uncertainties of traditional empirical cooling water pipe design, provides a comprehensive quantitative reference for engineering practice, and demonstrates strong versatility and engineering application value.